THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLE AND CRITICAL READING ABILITY - Yunda Lestari (STKIP PGRI Lubuklinggau, 2020)
This study aimed at the correlation between students’ learning style and critical reading ability. Correlational method was used in this study with descriptive correlational design. Test and questionnaire were used in collecting the data.The population was the fourth semester students of English Education Study Program of Teacher Training and Educational Faculty of Baturaja University in academic year 2018/2019 with the total of population was 20 students. Total sampling formula was used in taking the sample. Correlation level was used in finding out the correlation between students’ learning style and critical reading ability. Based on the result of the test, the students’ average score of test was 85.00. The students’ average score of questionnaire was 59.05 and it was in good category. The data showed that there was significant correlation between students’ learning style and critical reading ability. The correlation was significant in terms of the correlation coefficient level was 0.01. It meant that correlational is significant at the 0.01 level (2-tailed).